Construction and development - Field hockey specific skills' test - Mohan, L.; Murtaza, S. T.; Kumar Katiyar, A. (International Journal of Human Movement and Sports Sciences, 2021)
In this existing time, the approaches made in field hockey are highly appreciable. As the synthetic surface introduced, many drastic changes have taken place. The game got a new trend for assessing functional playing abilities, and performance-based specific skills of advanced field hockey players. Field hockey is a stick-based game; where stick-work with speed and accuracy is required for controlling the movement of the ball. A number of specific skill tests had already been developed and produced to test the functional abilities of players` stick-work with other developmental work as fielding, dribbling, driving, controlling, and shooting while moving the ball. However, no existing test fulfills the criteria of modern field hockey playing skills. In order to test the specific skills and evaluate the performance level of advanced hockey players; the authors designed and constructed a test with proper selection of specific skills, in which many other movements related to advance skills were combined with stick-work. Wherein major focus was laid upon the player`s ability to control the force element when contacting the ball, manipulation of stick-work by combining wrist and hand movement with quickness to control the movement of the ball while running in speed and hitting the right target was the prime concern. The idea presented in this paper is the need of the day and, the test is known as the `Veer- Lalit Field-Hockey Skills Test` which meaningfully analyses the overall performances of advanced hockey players.